New coronavirus infection (COVID-19) and kidney-urinary tract diseases / pathological conditions - D.I. Trukhan (LLC "MEDIAFORMAT", 2022)
The main target of the new coronavirus infection (COVID19), spread by the SARS-CoV-2 virus, is the respiratory system. SARS-CoV-2 infection can cause kidney damage, and severe renal dysfunction is more common in patients with chronic comorbid/multimorbid disease, especially in patients with chronic kidney disease. A search was made for literature on the association of major diseases (pathological conditions) of the kidneys and urinary tract with the new coronavirus infection COVID-19 in electronic search engines PubMed, Scopus, eLIBRARY. The found literary sources indicate that the new coronavirus infection COVID-19 certainly has a specific effect on the urinary system in general, and in particular, on certain diseases of the kidneys and urinary tract.